Characterization Of Clinical Treatments For Migraine Conducted In Brazil: An Ecological Study - Falcão, Stephanie Bezerra Muniz; Júnior, José Lima Silva; Paiva, Maria Anita Oliveira Souza; Martins, Larissa Pereira; Costa, Laína Adelaide Xavier da; Santos, Liriel Thaís Dantas dos; Oliveira, Déborah Ellen Lima de; Silva, Débora Vitória da; Alves, Jamilly Maria da Silva; Jasset, Karla Kelly Henrique; Pereira, José da Silva; Vasconcelos, Danilo de Almeida; et al. (Headache Medicine, 2023)
Full abstract in PDF.